1991
DOI: 10.1093/oxfordjournals.humrep.a137286
|View full text |Cite
|
Sign up to set email alerts
|

Block to development in cultured rat 1-cell embryos is overcome using medium HECM-1

Abstract: Rat pronuclear embryos were cultured in hamster embryo culture medium-1 (HECM-1) or a modified Krebs-Ringer bicarbonate solution (mKRB). Embryo cultures in HECM-1 were also challenged with low oxygen concentrations. In HECM-1, 57.9% (70/121) of the pronuclear embryos developed into the 4-cell stage after 48 h of culture. The rates of 8-cell, morula and blastocyst formation were 32.2% (39/121), 17.4% (21/121) and 9.9% (12/121), respectively. On the other hand, in mKRB, rat pronuclear embryos showed developmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(51 citation statements)
references
References 0 publications
0
51
0
Order By: Relevance
“…However, Brown and Whittingham (1992) (Kishi et al, 1991 Bavister, 1990), clear osmolar dependency is reported in mice with the optimum ranges of 250-280 mosmol for one-cell (Whitten, 1971) and [272][273][274][275][276][277][278][279][280] mosmol for two-cell (Biggers and Brinster, 1965;Brinster, 1965) embryos.…”
Section: Mediummentioning
confidence: 99%
See 1 more Smart Citation
“…However, Brown and Whittingham (1992) (Kishi et al, 1991 Bavister, 1990), clear osmolar dependency is reported in mice with the optimum ranges of 250-280 mosmol for one-cell (Whitten, 1971) and [272][273][274][275][276][277][278][279][280] mosmol for two-cell (Biggers and Brinster, 1965;Brinster, 1965) embryos.…”
Section: Mediummentioning
confidence: 99%
“…They obtained consistent development of hamster embryos in vitro beyond the two-cell and four-cell stages to the blastocyst stage in a modified Tyrode's medium that did not contain glucose and phosphate (Schini and Bavister, 1988;McKieman and Bavister, 1990; Bavister, 1990;Seshagiri and Bavister, 1991a). This new medium, designated as hamster embryo culture medium 1 (HECM-1; Schini and Bavister, 1988), was applied to the culture of rat (Kishi et al, 1991) and bovine (Pinyopummintr and Bavister, 1991;Kim et al, 1993) one-cell embryos in which development to the blastocyst stage was supported to a limited extent. However, it is not clear whether phosphate and glucose affect rat embryo development independently or in combi¬ nation.…”
Section: Introductionmentioning
confidence: 99%
“…In rats, early stage embryos could not be cultured before 1993, when developmental retardation, called '2-cell block', was overcome by application of hamster embryo culture medium (HECM-1) [6]. Then, Miyoshi et al modified HECM to obtain high percentages (>90%) of embryo development in vitro.…”
mentioning
confidence: 99%
“…In this study, to further improve embryo culture condition, the effects of oxygen tension and bovine serum albumin (BSA), two possibly important factors for embryo culture in other mammalian species [2], were examined using Wistar rats as a model, because Wistar rats have often been used for establishing the basic techniques of embryo and gamete manipulation [6,11]. Wistar rats from two breeders, Crlj:WI and Slc:Wistar, were used to examine whether or not their effects are -Note-consistent across colonies since some differences in developmental responses have been observed among rat strains [14], and these particular breeder colonies are likely to have different genetic backgrounds [16].…”
mentioning
confidence: 99%
“…It has been shown that uterine and oviduct surface oxygen concentrations ranged between 2 and 9 % [38]. In-vitro culture of embryos under low oxygen (5 %) as opposed to atmospheric oxygen (20 %) resulted in higher blastocyst formation rates in rats [39,40], mice [41,42], sheep and cattle [43]. Similarly, culture of embryonic or adult stem cells under low oxygen improved their growth and maintained their pluripotency [44].…”
Section: Discussionmentioning
confidence: 99%